Method for constructing three-dimensional structure material based on metal modified conjugated covalent organic plane Co-TCNB COF and application
By using metal-modified conjugated covalent organic plane to construct a three-dimensional structure Co-TCNB-PIP or Co-TCNB-PA material in the negative electrode material of lithium-ion battery, the existing materials have been solved in terms of Coulomb efficiency, specific capacity and stability. Inadequately, efficient electrochemical performance improvement has been achieved, suitable for the needs of high-performance lithium batteries.
Patent Information
- Application Number
- CN202311365330.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2024-12-13
AI Technical Summary
Existing lithium-ion battery anode materials such as graphite materials have low efficiency, low specific capacity and poor rate performance for the first time, which cannot meet the needs of high-performance batteries. In addition, covalent organic framework compounds use toxic solvents and catalysts during the synthesis process, and The π-π stacking of two-dimensional materials results in underutilization of internal active sites, limiting their electrochemical properties.
The preparation method of constructing three-dimensional structures of Co-TCNB-PIP or Co-TCNB-PA based on metal-modified conjugated covalent organic planes is adopted. The materials are synthesized easily and quickly through ultrasonic mixing and solvent-thermal method, and interlayer bridge ligand is introduced. Piperazine or pyrazine, form a stable three-dimensional structure, avoiding π-π stacking and promoting charge transfer.
It achieves high conductivity, low impedance and better ion diffusion kinetic characteristics, improves the initial capacity, first Coulomb efficiency and cycle stability of the material, and solves the volume of traditional materials during dense layer structure accumulation and lithium ion embedding and disengagement. Change issues, suitable for large-scale production and high-performance lithium battery applications.
Smart Images

Figure CN119119491A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of negative electrode materials for lithium ion batteries (LIBs) in energy storage materials, and in particular to a preparation method of a Co-TCNB-PIP or Co-TCNB-PA material having a three-dimensional structure based on a metal-modified conjugated covalent organic plane and its application as a negative electrode material for lithium ion batteries. Background Art
[0002] In today's era of rapid development of science and technology and productivity, the depletion and safety issues of fossil energy resources have become increasingly obvious. At the same time, fossil energy pollution is in conflict with today's green environmental protection concept. In order to meet the energy needs of production and life, it is necessary to develop green renewable energy. Since new energy sources such as solar energy, wind energy, water conservancy and tidal energy are intermittent, energy storage devices are needed to make up for the lack of new energy. At the same time, various portable electronic devices such as mobile phones, computers and sensors have put forward higher requirements for energy storage. Lithium batteries have been rapidly developed and put into practical use with their high capacity density, practicality and safety.
[0003] In the field of LIBs negative electrode materials, graphite-based negative electrode materials are still the most widely used in practice. They have the advantages of abundant reserves, low cost and stable electrochemical properties. However, they also have shortcomings such as low first coulombic efficiency, low specific capacity and poor rate performance. They cannot meet the needs of high-performance batteries and cannot adapt to the requirements of high volume density and high specific capacity of today's energy storage devices. Therefore, it is necessary to develop new negative electrode materials.
[0004] Covalent organic frameworks (COFs) are a new class of periodic ordered polymers. They are composed of light elements (C, H, O, N, etc.) and connected by strong covalent bonds to form periodic one-dimensional, two-dimensional or three-dimensional porous structures. Due to their environmental friendliness, high specific surface area and structural diversity, they have broad application prospects in gas adsorption, catalysts, drug delivery, energy storage and semiconductors. At the same time, COFs are also considered to be the most promising next-generation electrode materials for LIBs due to their advantages such as high porosity, excellent structural stability and high theoretical capacity. However, there are still some problems that limit their practical application, mainly the difficulty of synthesis and the use of toxic organic solvents and catalysts during the synthesis process, poor conductivity, severe π-π stacking between layers of traditional 2D COF materials, forming one-dimensional (1D) pore channels with minimal transport, and causing the internal active sites to be unable to be fully utilized, as well as the problem of volume change during lithium ion insertion and extraction, which to some extent limits their large-scale preparation and electrochemical performance. Therefore, the development of new electrode materials with simple preparation, strong conductivity, high actual capacity and good cycle stability is of great practical significance for the development of high-performance lithium batteries. Summary of the invention
[0005] Purpose of the invention: In view of the limitations and deficiencies of existing materials and technologies in applications, the present invention provides a method for preparing Co-TCNB-PIP or Co-TCNB-PA materials with three-dimensional structures based on metal-modified conjugated covalent organic planes. The Co-TCNB-PIP or Co-TCNB-PA materials prepared by the present invention not only have a simple and fast synthesis process, but also have a more stable three-dimensional structure, high conductivity and excellent cycle stability. The introduction of interlayer bridging ligands can not only effectively avoid the serious π-π stacking between planar materials to bury the internal active sites, and cause the problems of low actual specific capacity and poor cycle stability, but also provide a bridge for the transfer of interlayer charges, thereby showing high conductivity, low impedance and better ion diffusion kinetics.
[0006] The present invention also provides the preparation of the Co-TCNB-PIP or Co-TCNB-PA material with a three-dimensional structure based on a metal-modified conjugated covalent organic plane and its application as a negative electrode material for lithium-ion batteries.
[0007] Technical solution: In order to achieve the above-mentioned purpose, the present invention discloses a method for preparing a three-dimensional structure Co-TCNB-PIP or Co-TCNB-PA material as a negative electrode material for a lithium-ion battery based on a metal-modified conjugated covalent organic plane, comprising the following steps:
[0008] (1) adding 1,2,4,5-tetracyanobenzene (TCNB) and cobalt metal salt into an organic solution and mixing by ultrasonication to obtain a dispersion;
[0009] (2) heating the dispersion to react, cooling to room temperature, collecting the precipitate by centrifugation, and vacuum drying to obtain the metal-modified covalent organic planar material Co-TCNB COF;
[0010] (3) Co-TCNB COF and piperazine (PIP) or pyrazine (PA) are added to an organic / aqueous solution and reacted under the assistance of ultrasound. After the reaction, the three-dimensional structure materials of Co-TCNB-PIP or Co-TCNB-PA are obtained by centrifugation and vacuum drying.
[0011] Wherein, the cobalt metal salt in step (1) is one or more of cobalt nitrate hexahydrate, cobalt chloride hexahydrate or cobalt acetate tetrahydrate.
[0012] Preferably, the cobalt metal salt is cobalt nitrate hexahydrate.
[0013] Wherein, the organic solvent in step (1) is one or more of anhydrous ethanol, anhydrous methanol and ethylene glycol.
[0014] Preferably, the organic solvent is anhydrous ethanol.
[0015] Wherein, the molar ratio of the 1,2,4,5-tetracyanobenzene (TCNB) organic ligand and the metal salt in step (1) is 1:1 to 3:1.
[0016] Wherein, the molar ratio of the 1,2,4,5-tetracyanobenzene (TCNB) organic ligand and the metal salt in step (1) is 2:1.
[0017] The temperature of the heat preservation reaction process in step (2) is 140°C-180°C, and the reaction duration is 12-36h.
[0018] Preferably, the temperature selected for the insulation reaction is 160° C. and the reaction time is 24 h.
[0019] The mass ratio of the Co-TCNB COF to PIP is 20-25:3, and the mass ratio of the Co-TCNB COF to PA is 20-25:2.8-3.
[0020] Preferably, the Co-TCNB COF, PIP or PA in step (3) are 0.25 g, 0.03 g or 0.028 g respectively.
[0021] Wherein, the IPA and H2O described in step (3) are 10 mL respectively.
[0022] Wherein, the ultrasonic-assisted process parameters described in step (3) are set to 300-600W and the time is 20-40 minutes.
[0023] Preferably, the ultrasonic-assisted process parameters are set to 450W and the time is 30 minutes.
[0024] The rotation speed of the centrifugal collection product is 9000 r / min for 5-10 minutes, and hot ethanol, water and ethanol are used for washing multiple times in sequence during centrifugation.
[0025] Wherein, the vacuum drying process lasts for 12 hours at a temperature of 60-80°C.
[0026] The preparation method of the present invention is based on metal-modified conjugated covalent organic plane to construct a three-dimensional structure Co-TCNB-PIP or Co-TCNB-PA material.
[0027] The invention discloses an application of the Co-TCNB-PIP or Co-TCNB-PA material having a three-dimensional structure based on a metal-modified conjugated covalent organic plane in the field of negative electrode materials for lithium batteries.
[0028] The present invention proposes a preparation method for a three-dimensional structure Co-TCNB-PIP or Co-TCNB-PA material based on a metal-modified conjugated covalent organic plane as a negative electrode material for a lithium battery. First, a renewable and less polluting organic solvent such as anhydrous ethanol is used as a solvent to synthesize the Co-TCNB COF plane material by a simple one-step solvothermal method, and then an interlayer bridging ligand PIP or PA is introduced in water and IPA solvents by ultrasound to simply and quickly prepare a Co-TCNB-PIP or Co-TCNB-PA material with a stable three-dimensional structure. Different from the existing metal phthalocyanine and TM-TCNB materials that use small-scale synthesis methods such as molecular deposition and involve a large number of equipment in the synthesis process, and the use of toxic organic solvents and catalysts in the synthesis process of traditional COF materials, long reaction time and difficult synthesis, the preparation method of the present invention has the advantages of being green, environmentally friendly, low-cost, and simple and quick preparation. It conforms to the current concept of green and sustainable development and also provides the possibility for large-scale production and practical application of such materials.
[0029] The present invention selects 1,2,4,5-tetracyanobenzene (TCNB) nitrogen-rich organic ligand, which has a conjugated structure of a benzene ring and four cyano groups (-CN). The synthesis principle of the Co-TCNB-PIP or Co-TCNB-PA material based on metal-modified conjugated covalent organic plane to construct a three-dimensional structure is as follows: Figure 1 As shown. Since the presence of metal ions reduces the activation energy of the reaction, TCNB can form a covalent organic network that expands the macrocyclic conjugated system in a green anhydrous ethanol solvent without using a catalyst. This covalent organic network further combines with transition metal ions to form a metal-centered covalent organic TM-TCNB conjugated structure. For the central metal atom, a cobalt metal central atom with an atomic radius close to the central gap radius of the macrocyclic ring is selected. The cobalt atom is combined with the nitrogen atom in the macrocyclic ring in the form of Co-N tetracoordination. The degree of conjugation of this metal-modified covalent organic network structure is further enhanced. Co-TCNB has excellent metallic properties, low band energy, abundant lithium storage sites and stable chemical properties.
[0030] The present invention selects piperazine (PIP) or pyrazine (PA) as an interlayer bridging ligand, and its non-conjugated system structure enables it to better combine with the metal center inside the conjugated plane of Co-TCNB to form a Co-TCNB-PIP or Co-TCNB-PA material with a three-dimensional structure, which can effectively solve the problem that the two-dimensional Co-TCNB COF negative electrode material has densely stacked layer structures, forms a one-dimensional (1D) hole channel with low transferability, and causes a large number of internal active sites to accumulate and be buried, thereby affecting its actual electrochemical performance. It has better structural stability, uniformly distributed active sites, better interlayer charge transfer and multi-dimensional ion diffusion paths. Thus, it exhibits higher initial capacity, higher first coulomb efficiency and stronger cycle stability, as well as better ion diffusion kinetics.
[0031] The present invention focuses on using specific non-conjugated piperazine (PIP) or conjugated pyrazine (PA) organic molecules, introducing them as interlayer bridging ligands into metal-modified conjugated covalent planar network (Co-TCNB COF) materials, and preparing Co-TCNB-PIP or Co-TCNB-PA materials with three-dimensional structures as negative electrode materials for lithium batteries, which have better electrochemical properties than Co-TCNB COF two-dimensional planar materials. The present invention proposes a new method for optimizing planar covalent organic electrode materials, which is different from the existing stripping methods that have no sustained effect on two-dimensional materials or complicated preparation processes. It also proposes a new method for constructing a three-dimensional covalent organic framework, which can effectively solve the problem of a severe shortage of 3D building units and greatly enrich the types of 3D COF materials.
[0032] The present invention is based on a simple and green synthesized metal-modified conjugated covalent planar network (Co-TCNB COF) material. By introducing a specific non-conjugated system piperazine (PIP) or conjugated pyrazine (PA) bridging ligand between layers, and using ultrasound to assist, Co-TCNB-PIP and Co-TCNB-PA materials with stable three-dimensional structures are synthesized simply and quickly. Different from the synthetic limitations of the existing materials such as complex preparation process, long synthesis time and multiple synthesis equipment, it provides a possibility for the practical application of such materials. At the same time, the use of toxic organic solvents and catalysts is avoided, and pollution is avoided while reducing costs, which is in line with the concept of current green cycle development. In view of the problems of low initial capacity, low first coulomb efficiency and poor cycle stability caused by severe π-π stacking phenomenon of planar materials, the three-dimensional structure of the Co-TCNB-PIP or Co-TCNB-PA material of the present invention can effectively solve the stacking problem, has a widened interlayer spacing and a more stable structure, can effectively avoid the problem of electrode volume change caused by lithium ion insertion and removal during the cycle, and at the same time, the interlayer bridging ligand can play the role of a charge transfer bridge between planes to promote the transfer of charges and ion transfer. Therefore, the material of the present invention exhibits higher initial capacity, high conductivity and better cycle stability, as well as better ion diffusion kinetics. This is also the first time that such material has been applied in the field of negative electrode active materials for lithium-ion batteries.
[0033] Beneficial effects: Compared with the prior art, the present invention has the following advantages:
[0034] The present invention provides for the first time a method for preparing a Co-TCNB-PIP or Co-TCNB-PA material with a three-dimensional structure based on a metal-modified conjugated covalent organic plane, and for the first time uses the material as a lithium-ion negative electrode material. The present invention obtains a metal-modified conjugated covalent organic network (Co-TCNB COF) material by a simple one-step solvothermal method, and further introduces an interlayer bridging ligand PIP or PA with the assistance of ultrasound to obtain a three-dimensional structured Co-TCNB-PIP and Co-TCNB-PA material. The preparation process of the present invention is simple, fast, and low-cost. Renewable solutions such as ethanol are selected as solvents, which avoids environmental pollution and harm to the human body caused by the use of toxic solvents, and provides possibilities for the industrial preparation and practical application of such materials.
[0035] The three-dimensional structure Co-TCNB-PIP and Co-TCNB-PA lithium battery negative electrode materials prepared by the present invention are different from the existing graphite materials with low energy density and the two-dimensional covalent organic electrode materials with high theoretical capacity, but poor actual specific capacity, low conductivity and stability. The conjugated covalent organic three-dimensional structure COF material of the present invention has an electron-rich center rich in nitrogen atoms and combined with metal ions, and the bridging ligand can promote the transfer of interlayer electrons / charges, so that the entire structure has high conductivity. In addition, its three-dimensional structure fundamentally solves the stacking problem existing in 2D COF materials, and has better stability than the structure of two-dimensional materials, and can alleviate the changes in electrode volume caused by the insertion and extraction of lithium ions during the charge and discharge cycle, and the problems such as poor battery stability, poor cycle life and safety brought about by it, and shows higher initial capacity, better cycle stability and ion diffusion kinetics. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a schematic diagram of the synthesis of the three-dimensional structured Co-TCNB-PIP or Co-TCNB-PA material prepared by the present invention based on metal-modified conjugated covalent organic planes.
[0037] Figure 2 This is a SEM image of the Co-TCNB-PIP material with a three-dimensional structure based on a metal-modified conjugated covalent organic plane prepared by the present invention;
[0038] Figure 3 The Fourier transform infrared (FT-IR) image of the Co-TCNB-PIP material with a three-dimensional structure based on a metal-modified conjugated covalent organic plane prepared by the present invention;
[0039] Figure 4 The polycrystalline X-ray diffraction (PXRD) pattern of the Co-TCNB-PIP material with a three-dimensional structure based on a metal-modified conjugated covalent organic plane prepared in the present invention;
[0040] Figure 5 The X-ray photoelectron spectroscopy analysis (XPS) diagram of the Co-TCNB-PIP material with a three-dimensional structure based on a metal-modified conjugated covalent organic plane prepared in the present invention;
[0041] Figure 6 The Co-TCNB-PIP material prepared by the present invention based on the metal-modified conjugated covalent organic plane to construct a three-dimensional structure is in the range of 0.01-3.00 V with a scan rate of 0.2 mV s -1 Cyclic voltammetry curve of .
[0042] Figure 7 The Co-TCNB-PIP material prepared by the present invention based on the metal-modified conjugated covalent organic plane to construct a three-dimensional structure is 200mA g-1 Constant current charge-discharge curve at a current density of;
[0043] Figure 8 The Co-TCNB-PIP material prepared by the present invention based on the metal-modified conjugated covalent organic plane to construct a three-dimensional structure is 200mA g -1 Performance diagram after 100 cycles at a current density of;
[0044] Fig. 9 The Co-TCNB-PIP material prepared by the present invention based on the metal-modified conjugated covalent organic plane to construct a three-dimensional structure is 1000mA g -1 Performance diagram after 800 cycles at a current density of;
[0045] Fig.10 The present invention discloses the rate performance of the Co-TCNB-PIP material with a three-dimensional structure constructed based on a metal-modified conjugated covalent organic plane at different current densities.
[0046] Fig.11 This is the AC impedance diagram of the Co-TCNB-PIP material with a three-dimensional structure constructed based on a metal-modified conjugated covalent organic plane prepared in the present invention before cycling.
[0047] Fig.12 The Co-TCNB-PA material prepared by the present invention based on the metal-modified conjugated covalent organic plane to construct a three-dimensional structure is 200mA g -1 Cycling performance diagram under current density of;
[0048] Fig.13 The Co-TCNB-PA material prepared by the present invention based on the metal-modified conjugated covalent organic plane to construct a three-dimensional structure is 1000mA g -1 Cycling performance diagram under current density of;
[0049] Fig.14 The present invention discloses the rate performance of the Co-TCNB-PA material with a three-dimensional structure constructed based on a metal-modified conjugated covalent organic plane at different current densities. DETAILED DESCRIPTION
[0050] The present invention is further described below in conjunction with specific embodiments and drawings.
[0051] The experimental methods described in the examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0052] Among them, anhydrous ethanol, 1,2,4,5-tetracyanobenzene (TCNB), cobalt nitrate hexahydrate, isopropyl alcohol (IPA), piperazine (PIP), pyrazine (PA), Ketjen black, polyvinylidene fluoride (PVDF, average molecular weight 400,000 to 500,000), N-methylpyrrolidone (NMP), etc. were purchased from Aladdin Chemical Reagent Network.
[0053] Example 1
[0054] The specific preparation steps of a three-dimensional structure Co-TCNB-PIP material based on metal-modified conjugated covalent organic plane are as follows:
[0055] (1) Dissolve Co(NO3)2·6H2O (0.5 mmol, 0.153 g) in anhydrous ethanol solvent (30 mL) and dissolve it completely by ultrasonication. Then add 1,2,4,5-tetracyanobenzene (TCNB) (1 mmol, 0.178 g) to the solution and disperse it completely by ultrasonication. The dispersion is quickly poured into a 50 mL polytetrafluoroethylene liner and sealed in a hydrothermal reactor. The reactor is placed in a forced air drying oven at 160°C and maintained for 24 hours.
[0056] (2) After the reaction is completed and the temperature drops to room temperature, open the reactor and transfer the dispersion into a 50 mL centrifuge tube. -1 The solid was collected by centrifugation at a speed of 10 min, and the crude product was washed by centrifugation with hot ethanol solution, deionized water and ethanol respectively. Finally, the product was placed in a vacuum drying oven at 70°C for 12 hours to obtain a black-green solid powder Co-TCNB COF material.
[0057] (3) Weigh 0.25 g of Co-TCNB COF material and 0.03 g of piperazine in turn and put them into a beaker containing 10 mL of isopropanol and deionized water, then directly transfer the beaker to an X0-650D ultrasonic cell disruptor, and set the parameters to a 6-amplitude variable rod, 450 W ultrasonic power, and 30 minutes of working time. After the reaction is completed and cooled to room temperature, transfer the mixed solution to a centrifuge tube and centrifuge the dispersion at 9000 r min. -1 The solid crude product was collected by centrifugation at a speed of 10 min, and then the crude product was washed by centrifugation with H2O and EtOH solutions for multiple times. The product was transferred to a vacuum oven and stored at 60 degrees Celsius for 12 hours to obtain a dark green solid powder Co-TCNB-PIP product.
[0058] Figure 2The SEM image of the Co-TCNB-PIP material with a three-dimensional structure based on the Co-TCNB plane prepared in the present invention shows that the spherical Co-TCNB (i.e., the black-green solid powder Co-TCNB COF material prepared in step 2) and the planar material ( Figure 2 a, b), after the introduction of interlayer bridging ligands, the three-dimensional structure of Co-TCNB-PIP material shows a new morphology of etched surface of the ball ( Figure 2 c, d); Figure 3 The FT-IR image of the three-dimensional structure Co-TCNB-PIP material prepared in the present invention is shown in FIG. Figure 3 It can be seen that at 722, 1090, 1337, 1468, 1520 and 1640 cm -1 The characteristic peaks of the unit phthalocyanine ring are shown at 808 and 914 cm -1 The characteristic peaks of Co-TCNB-PIP materials are assigned to the vibration of the metal coordination bond Co-N, which fully indicates the formation of metal-modified conjugated Co-TCNB materials. Based on the Co-TCNB planar material spectrum, the Co-TCNB-PIP materials have the peaks at 2980 cm -1 The characteristic peaks of CH vibration on saturated carbon are shown near 1550, 1450, 1390, 1310 and 1130 cm -1 The nearby peaks show enhanced characteristic peaks of CC and CN structures. Figure 4 The PXRD pattern of the Co-TCNB-PIP material prepared by the present invention, which constructs a three-dimensional structure based on the Co-TCNB plane, shows obvious characteristic peaks at small angles near 5.8° and 7.7°, and has a broad peak at about 27.3°. Based on its spectrum, the Co-TCNB-PIP material shows a decrease in the intensity of the small-angle diffraction peak, and a broad peak at about 26.4°. This may be because the addition of the interlayer bridging ligand destroys part of the stacking structure to a certain extent, thereby affecting the crystallinity. In addition, the Co-TCNB-PIP material shows the interlayer spacing information of the three-dimensional structure and the diffraction peaks unique to the crystal plane of the bridging ligand PIP at about 11.3° and 36.2°, respectively. The above characterization fully demonstrates that the bridging ligand PIP was successfully introduced on the basis of the Co-TCNB plane to form a new substance Co-TCNB-PIP.
[0059] Figure 5 This is the XPS graph of the Co-TCNB-PIP material with a three-dimensional structure based on the Co-TCNB plane prepared in the present invention. From the Co 2p and N1s spectra, it can be seen that the Co-TCNB material shows obvious signal peaks at around 781.4eV and 797.2eV and its strong accompanying satellite peaks. These two signal peaks correspond to the 2p 3 / 2 and 2p1 / 2 orbitals, indicating that the cobalt ions in the material structure are mainly Co 2+ Cobalt metal exists in the center of the planar network unit structure in a four-coordinated connection. The Co atoms in the Co-TCNB-PIP material have Co 2p 3 / 2 and Co 2p 1 / 2 The characteristic peak of the spin orbit and its satellite peaks are not observed, but the intensity and area ratio of the characteristic main peak and its corresponding satellite peak are increased, which may be due to the presence of positive trivalent cobalt without satellite peaks in diamagnetic properties, and the increase in the strength and proportion of the N-Co bond. The above XPS results further show that the Co-TCNB-PIP material maintains the structure of the Co-TCNB material while introducing a bridging ligand. The bridging ligand is converted to Co 3+ Co 2+ The metal center forms a six-coordinated inner-orbital complex, constructing a more stable three-dimensional structure.
[0060] Example 2
[0061] The electrochemical performance of the Co-TCNB-PIP material prepared in the present invention as a negative electrode material for LIBs was tested.
[0062] Test steps: The Co-TCNB-PIP material prepared in Example 1 is used as the active material. About 35 mg of the active material is weighed according to the mass ratio of active material: Ketjen black: polymer binder (polyvinylidene fluoride, PVDF) of 7:2:1. It is fully ground in a mortar, and an appropriate amount of NMP (N-methylpyrrolidone) of about 350 μL is added as a solvent to fully dissolve the binder. Stir for 12 hours to make it evenly mixed to obtain a slurry with a flow tendency; the slurry is coated on the rough surface of the copper foil by a film drawing device, and the 150 μm surface is selected by the four-sided film drawing device. The coated film is kept at 70°C in a vacuum drying oven for more than 10 hours to fully evaporate the solvent, and then the copper foil coated with the active material is cut into electrode sheets with a diameter of 12 mm by a slicer, and the mass of the active material on each electrode sheet is controlled to be between 0.6-1.0 mg. For the assembly of lithium-ion batteries, Celgard2600 and lithium sheets are used as battery separators and counter electrodes, respectively, and the electrolyte is 1 mol L -1 The LiPF6 solution (ethylene carbonate / dimethyl carbonate / diethyl carbonate V:V:V=1:1:1) was used for the battery assembly in a glove box at an ambient temperature of 25°C, and the oxygen and moisture contents were both less than 1ppm. The LAND CT 2001A blue electric system was used for constant current charge and discharge tests, and the CHI660E electrochemical workstation was used for cyclic voltammetry (voltage range 0.01~3.0V, scan rate 0.2mV s -1) and impedance (frequency range 0.01 Hz to 100 kHz). At the same time, the Co-TCNB COF prepared in Example 1 was directly used to prepare an electrode in the same manner as in Example 2 as a control for testing, i.e., no piperazine was added, and Co-TCNB was used in the following figures to represent it.
[0063] Figure 6 The Co-TCNB-PIP material with a three-dimensional structure based on the Co-TCNB plane prepared by the present invention has a voltage range of 0.01-3V and a scan rate of 0.2mV s -1 The cyclic voltammetry curve of Figure 6 It can be seen that the CV curves of the two have the same trend and redox potential, and both show obvious and irreversible strong reduction peaks, which is due to the irreversible reaction during the first cycle to form a solid electrolyte membrane (SEI). However, the CV curve of the Co-TCNB electrode shows a more obvious change in the curve range and a shift in the redox peak as the cycle progresses, indicating that it has an obvious activation process. The absolute area between the cyclic voltammetry curves of the Co-TCNB-PIP electrode material is larger, indicating that it has a more complete contact with the electrolyte. Figure 7 The charge-discharge curve of the Co-TCNB-PIP material with a three-dimensional structure based on the Co-TCNB plane prepared by the present invention. From the figure, it can be seen that the first discharge-charge specific capacities of the Co-TCNB and Co-TCNB-PIP electrodes are 820.7 / 319.6 mAh g -1 and 2173.3 / 1200.6mAh g -1 , the first Coulombic efficiency was 38.9% and 55.2% respectively. The Co-TCNB-PIP material with the introduction of interlayer bridging ligands was significantly better than Co-TCNB, with higher initial charge and discharge capacity and higher first Coulombic efficiency.
[0064] Figure 8 The Co-TCNB-PIP material prepared by the present invention, which is a three-dimensional structure based on the Co-TCNB plane, is subjected to 200 mA g -1 The performance diagram of the Co-TCNB-PIP electrode is shown in Figure 1. The Co-TCNB-PIP electrode can obtain 764.8 mAh g after 100 cycles. -1 The stable reversible specific capacity is better than that of Co-TCNB. Fig. 9 The Co-TCNB-PIP material prepared by the present invention, which is a three-dimensional structure based on the Co-TCNB plane, is subjected to 1000 mA g -1 The Co-TCNB-PIP electrode can maintain 418.6 mAh g after 800 cycles. -1Its specific capacity, stability and reversible specific capacity are significantly better than those of Co-TCNB. Fig.10 The rate performance diagram of the Co-TCNB-PIP material with a three-dimensional structure based on the Co-TCNB plane prepared in the present invention at different current densities shows that the average specific capacities of the Co-TCNB-PIP electrode are 1067.2, 745.5, 523.2, 353.5 and 258.6 mAh g -1 When the current density is increased from 4000mA g -1 Restore back to 200mAg -1 , with 767.1mAh g -1 The stable reversible specific capacity of Co-TCNB was restored to 200 mA g -1 When the reversible specific capacity is only 510 mAh g -1 From the above electrochemical cycle characterization, it can be concluded that the Co-TCNB-PIP electrode has better cycle stability and its effect is significantly superior to Co-TCNB.
[0065] Fig.11 This is the AC impedance test diagram of the Co-TCNB-PIP material with a three-dimensional structure based on the Co-TCNB plane prepared by the present invention before cycling. It can be seen from the figure that the charge transfer impedance value of the Co-TCNB-PIP electrode in the semicircle of the high-frequency region is significantly smaller than that of the Co-TCNB electrode, and the slope of the oblique line of the Co-TCNB-PIP electrode in the low-frequency region is smaller, and it has a smaller ion diffusion impedance. It can be concluded that the Co-TCNB-PIP material after the introduction of the bridging ligand has low impedance, high conductivity and better ion diffusion kinetics when used as a negative electrode material for LIBs.
[0066] Example 3
[0067] The preparation method of Example 3 is the same as that of Example 1, except that: the cobalt metal salt in step (1) is cobalt chloride hexahydrate, the solvent is anhydrous methanol solution, the hydrothermal reaction kettle is placed in a forced air drying oven and heated to 140° C.; and the reaction time is 36 hours.
[0068] In the ultrasonic-assisted reaction of step (3), the parameters are set to an ultrasonic power of 300 W and a working time of 40 minutes.
[0069] Example 4
[0070] The preparation method of Example 3 is the same as that of Example 1, except that: the cobalt metal salt in step (1) is cobalt acetate tetrahydrate, the solvent is ethylene glycol solution, the hydrothermal reaction kettle is placed in a forced air drying oven and heated to 180° C.; and the reaction time is 12 hours.
[0071] In the ultrasonic-assisted reaction of step (3), the parameters are set to an ultrasonic power of 600 W and a working time of 20 minutes.
[0072] Example 5
[0073] The preparation method of Example 5 is the same as that of Example 1, except that 0.03 g of piperazine (PIP) described in step (3) is replaced with 0.028 g of pyrazine (PA) to obtain a solid powder Co-TCNB-PA product.
[0074] Example 6
[0075] The electrochemical performance of the Co-TCNB-PA material prepared in the present invention as a negative electrode material for LIBs was tested.
[0076] The preparation method of Example 6 is the same as that of Example 2, except that in the test step, the Co-TCNB-PA prepared in Example 5 is used as the electrode active material.
[0077] Fig.12 The Co-TCNB-PA material prepared by the present invention, which is based on the Co-TCNB plane to construct a three-dimensional structure, is subjected to 200 mA g -1 The performance diagram of 116 cycles at a current density of 1.38 Å is shown in the figure. It can be seen from the figure that the Co-TCNB-PA electrode obtains 1632 mAh g after 116 cycles. -1 Stable reversible specific capacity. Fig.13 The Co-TCNB-PA material prepared by the present invention, which is based on the Co-TCNB plane to construct a three-dimensional structure, is subjected to 1000 mA g -1 The Co-TCNB-PIP electrode can maintain 1376 mAh g after 593 cycles. -1 Specific capacity. Fig.14 The figure shows the rate performance of the Co-TCNB-PA material with a three-dimensional structure based on the Co-TCNB plane prepared in the present invention at different current densities. It can be seen from the figure that the average specific capacities of the Co-TCNB-PA electrode are 1157, 828, 670, 518 and 260 mAh g -1 When the current density is increased from 4000mA g -1 Recover back to 200mA g -1 1243mAh g -1 From the above electrochemical cycle characterization, it can be concluded that the Co-TCNB-PA electrode has better specific capacity and cycle stability than Co-TCNB-PIP, and is also much better than the negative electrode prepared by Co-TCNB material.
Claims
1. A method for preparing a three-dimensional structure Co-TCNB-PIP or Co-TCNB-PA material based on metal-modified conjugated covalent organic plane, characterized in that: The following steps are involved: (1) adding 1,2,4,5-tetracyanobenzene (TCNB) and cobalt metal salt into an organic solution and mixing by ultrasonication to obtain a dispersion; (2) heating the dispersion to react, cooling to room temperature, collecting the precipitate by centrifugation, and vacuum drying to obtain the metal-modified covalent organic planar material Co-TCNB COF; (3) Co-TCNB COF and piperazine (PIP) or pyrazine (PA) were added to an organic solvent / aqueous solution, respectively, and reacted under the assistance of ultrasound. After the reaction, the three-dimensional structure materials of Co-TCNB-PIP or Co-TCNB-PA were obtained by centrifugation and vacuum drying.
2. The method for preparing a Co-TCNB-PIP or Co-TCNB-PA material based on a metal-modified conjugated covalent organic plane to construct a three-dimensional structure according to claim 1, characterized in that: The cobalt metal salt is any one or more of cobalt nitrate hexahydrate, cobalt chloride hexahydrate or cobalt acetate tetrahydrate.
3. The method for preparing a Co-TCNB-PIP or Co-TCNB-PA material based on a metal-modified conjugated covalent organic plane to construct a three-dimensional structure according to claim 1, characterized in that: The organic solvent is preferably any one or more of anhydrous ethanol, anhydrous methanol or ethylene glycol.
4. The method for preparing a Co-TCNB-PIP or Co-TCNB-PA material based on a metal-modified conjugated covalent organic plane to construct a three-dimensional structure according to claim 1, characterized in that: The molar ratio of the 1,2,4,5-tetracyanobenzene (TCNB) organic ligand and the cobalt metal salt described in the preparation step is 1:1 to 3:
1.
5. The method for preparing a Co-TCNB-PIP or Co-TCNB-PA material based on metal-modified conjugated covalent organic plane to construct a three-dimensional structure according to claim 1, characterized in that: The ultrasonic mixing process described in step (1) takes 10-30 minutes to obtain a uniform dispersion.
6. The method for preparing the Co-TCNB-PIP or Co-TCNB-PA material based on metal-modified conjugated covalent organic plane to construct a three-dimensional structure according to claim 1, characterized in that: Step (2) heating the dispersion at a temperature of 140° C. to 180° C. for a duration of 12 to 36 hours.
7. The method for preparing a Co-TCNB-PIP or Co-TCNB-PA material based on metal-modified conjugated covalent organic plane to construct a three-dimensional structure according to claim 1, characterized in that: The mass ratio of the Co-TCNB COF to PIP is 20-25:3, and the mass ratio of the Co-TCNB COF to PA is 20-25:2.8-3.
8. The method for preparing a Co-TCNB-PIP or Co-TCNB-PA material based on metal-modified conjugated covalent organic plane to construct a three-dimensional structure according to claim 1, characterized in that: The ultrasonic-assisted process described in step (3) is set at 300-600W for 20-40 minutes.
9. A three-dimensional structured Co-TCNB-PIP or Co-TCNB-PA material based on a metal-modified conjugated covalent organic plane prepared by the preparation method of claim 1.
10. Application of the Co-TCNB-PIP or Co-TCNB-PA material with a three-dimensional structure based on a metal-modified conjugated covalent organic plane according to claim 9 in the field of negative electrode materials for lithium batteries.
